Exploring Family Functioning in Adolescent Dating Violence: A Case Study of an Indonesian Spiritual Community - Sejati, Putri Eka; Laisuwannachart, Panjarut; Zaw, Kaung; Yudaningsih, Titik (Knowledge Dynamics, 2025)
Background: Adolescence is a period of transition from childhood to adulthood. One of the significant changes during this period is changes in behavior related to sexual life. Adolescent sexual behavior that is almost identical to adolescence is dating behavior. Dating relationships are colored by cases of violence, especially by men. According to UN Women (2021) shows that at least 736 million women, and 87% of them are committed by people closest to them, including dating violence. Family Functioning is the quality of relationships between family members, one of which is the role of parents in preventing dating violence because parents are the first place of socialization before children socialize with the outside environment. Therefore, this study aims to explore the impact of Family Functioning on dating violence behavior among adolescents. Methods: This study employed a case study approach. Data collection was performed between November 2023 and March 2024 through in-depth interviews with two groups: one adolescent who had experienced dating violence and another who had not. Results: The finding found that adolescent who experienced dating violence came from dysfunctional families, while adolescent who did not experience dating violence were from families with higher levels of family functioning. Conclusions: The study indicates that adolescents from dysfunctional families are more prone to dating violence, while those from well-functioning families are less affected. This emphasizes the critical role of family dynamics in adolescent experiences. Future research should develop interventions to enhance family functioning and examine these dynamics across various cultural settings.